Đào tạo tín chỉ và mối quan hệ của thư viện với các khoa trong trường đại học - Phạm, Thị Mai (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Evaluates the role of libraries in education; analyzes the relationship between library and special faculties as well as liaising role of librarians with these faculties in training activity; sets forth measures to enhance effectiveness of this relationship.